2011
DOI: 10.1111/j.1365-2362.2011.02535.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of microRNA-21 in various carcinomas: a systematic review and meta-analysis

Abstract: Our findings suggest that miR-21 detection has a prognostic value in patients with cancer, especially in HNSCC and digestion system cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
109
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 50 publications
(90 reference statements)
5
109
1
Order By: Relevance
“…Our previous meta-analysis has shown that elevated expression of miR-21 was a predictor for worse outcome in a variety of cancers, especially in digestive system cancers and head and neck cancers [44]. In some studies, miR-155 was combined with miR-21 or a panel of miRNAs to predict survival [13,14,17,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous meta-analysis has shown that elevated expression of miR-21 was a predictor for worse outcome in a variety of cancers, especially in digestive system cancers and head and neck cancers [44]. In some studies, miR-155 was combined with miR-21 or a panel of miRNAs to predict survival [13,14,17,[34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, RT-qPCR analysis indicated that miR-21 expression was upregulated in BC tissues compared with that of normal bladder tissues. In particular, miR-21 has been shown to be involved in various cancer-associated processes, including cell growth, invasion and apoptosis (14). miR-21 induces hepatocellular carcinoma HepG2 cell proliferation via the suppression of mitogen-activated protein kinase-kinase 3 (15).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, by analyzing the serum from 12 acute pancreatitis patients and three healthy controls, Liu et al [46] identified miR7 as one of the three diagnostic and prognostic biomarkers. Although several systematic reviews [44,[47][48][49] have investigated biomarkers for GC, none has shown that miR-7 could be a biomarker of GC.…”
Section: Circulatory Biomarkermentioning
confidence: 99%